Helix Gear Wear Analysis On Line Boring Machine At PT. SSC WORKS Salok Api (Jurnal Rekayasa Mesin dan Inovasi Teknologi, 2021)
Line boring is a process of enlarging a hole using a single cutting tool that is held by a shaft resting on two or more bearings. The study was carried out on the wear rate that occurs on a 2 inch line boring shaft gear box that has been used for 3 years or 5,760 hours. The object used as research material is the helix gear in line boring gearboxes. The purpose of this study was to determine the wear on the helix gear line boring machine components and to determine the service life of the helix gear line boring machine components and to determine the factors that cause wear on the helix gear line boring machine components.       The research was conducted at PT. SSC WORKS Salok Api from 12 November 2020 to 20 December 2020. This research was carried out by testing and comparison of a gear by comparing two gears in terms of weight and volume as well as other parameters to determine the value of the wear rate and the life of the gear.       The factors that cause wear on the helix gear are not carrying out the surface hardening process to increase the hardness of the helix gear tooth surface, the lubrication contained in the helix gear gearbox cannot reduce the heat that arises, the construction on the inside of the gearbox is not quite right. The wear rate that occurs in the driven helix gear is 0.000219 mm / hour and is 0.000153 mm / hour for the driven helix gear. The service life limit for driven helix gear is 1,369 hours while the helix gear driven life limit is 1960 hours.